An Analysis of the Optimal Mix of Global Energy Resources and the Potential Need for Geoengineering Using the CEAGOM Model. Issue 8 (13th November 2017) - Anasis, John G.; Khalil, Mohammad Aslam Khan; Lendaris, George G.; Butenhoff, Christopher L.; Bluffstone, Randall
Abstract: Humanity faces tremendous challenges as a result of anthropogenic climate change caused by greenhouse gas emissions. The mix of resources deployed in order to meet the energy needs of a growing global population is key to addressing the climate change issue. The goal of this research is to examine the optimal mix of energy resources that should be deployed to meet a forecast global energy demand while still meeting desired climate targets. The research includes the unique feature of examining the role that geoengineering can play in this optimization. The results show that some form of geoengineering is likely to be needed by the middle of the 21st century as part of the optimal energy strategy in order to meet a specified climate goal of 580 ppm CO2 ‐eq greenhouse gas concentration (or ≈2 °C average global temperature rise). The optimal energy mix would need to rely on energy efficiency, nuclear, geothermal, hydro, and wind energy for over 50% of global energy needs. In addition, the overall cost of the optimal energy mix is sensitive to the assumed amount of achievable energy efficiency, carbon taxes, deployment of electric vehicles, and the assumed discount rate. Abstract : A unique analysis of what an optimal mix of global energy resources might be for the 21st century while staying within a 2 °C global temperature rise. It includes the potential role geoengineering can play as a means of meeting desired climate targets while minimizing the overall cost of the global energy system.